2010
DOI: 10.1007/s10886-010-9874-3
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Phenylpropanoid and Sesquiterpenoid Volatiles in Male Rectal Pheromonal Glands of the Guava Fruit Fly, Bactrocera correcta

Abstract: The guava fruit fly, Bactrocera correcta, is widely distributed in Thailand and other surrounding Southeast Asian countries, and, like the closely related sympatric species, the oriental fruit fly, B. dorsalis, infests various fruits, including guava, peach, and mango. Males of both B. correcta and B. dorsalis are strongly attracted to, and compulsively feed on, methyl eugenol (ME). Bactrocera dorsalis males fed on ME sequester its metabolite phenylpropanoids, (E)-coniferyl alcohol and 2-allyl-4,5-dimethoxyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Interestingly, Z-DMC found in B. correcta was also detected occasionally as a trace component in the rectal gland of B. dorsalis males fed on ME; but only in very few individuals (Nishida et al 1988b). These studies should, however, consider that males of B. correcta have relatively more complicated sex pheromonal components than B. zonata in that, besides the two ME metabolites, it also accumulates large quantities of sesquiterpene hydrocarbons possibly incorporated pharmacophagously from various plant sources during its adult stage (Tokushima et al 2010). Differentiating the three species, B. correcta, B. dorsalis and B. zonata, chemotaxonomically by checking the composition of phenylpropanoid volatiles accumulated in their rectal glands after exposure to ME is a very sensitive and precise method compared with methods based on indistinct morphological characters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Z-DMC found in B. correcta was also detected occasionally as a trace component in the rectal gland of B. dorsalis males fed on ME; but only in very few individuals (Nishida et al 1988b). These studies should, however, consider that males of B. correcta have relatively more complicated sex pheromonal components than B. zonata in that, besides the two ME metabolites, it also accumulates large quantities of sesquiterpene hydrocarbons possibly incorporated pharmacophagously from various plant sources during its adult stage (Tokushima et al 2010). Differentiating the three species, B. correcta, B. dorsalis and B. zonata, chemotaxonomically by checking the composition of phenylpropanoid volatiles accumulated in their rectal glands after exposure to ME is a very sensitive and precise method compared with methods based on indistinct morphological characters.…”
Section: Discussionmentioning
confidence: 99%
“…An authentic sample of (Z)-coniferyl alcohol was obtained by stereo-selective synthesis (Tokushima et al 2010). Samples of synthetic 2-allyl-4,5-dimethoxyphenol and (E)-coniferyl alcohol were prepared previously (Nishida et al 1988a, b).…”
Section: Field Trapping Of Wild Male Fliesmentioning
confidence: 99%
“…71,72) A series of sesquiterpene hydrocarbons such as β-caryophyllene (47) was identified from the rectal gland of wild B. correcta males. 73) These pharmacophagously acquired rectal sequestrates (both phenylpropanoids and sesquiterpenes) were suggested to function possibly as a unique sex pheromone to attract conspecific females of this highly diverged species radiating from central Southeast Asia. Compound 47 was found to be a more attractive male lure than 44 in B. correcta, and 47 thus serves as a highly selective monitoring agent not attractive to other sympatric pest species in Thailand (unpublished results).…”
Section: Plant-derived Sex Pheromonesmentioning
confidence: 99%
“…Methyl eugenol is also a parapheromone and feeding attractant for the guava fruit fly, Bactrocera correcta (Bezzi). Tokushima et al (2010) found that methyl eugenol metabolites, which were different from those sequestered by B. dorsalis, and also sesquiterpenes including α-humulene and β-caryophylene were sequestered in the male pheromonal rectal glands. In contrast, male C. capitata do not interact with essential oils that contain α-copaene, and unless the α-copaene is present in a low concentration, males tend to arrest near the essential oil but not contact it (e.g., Steiner et al, 1957).…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that presence of α-copaene as a contaminant in their sample may explain the observed attraction (Cossé et al, 1995). Grové et al (1998) subsequently showed that Tokushima et al 2010;3 Ibrahim et al 2010 male C. capitata were not attracted by β-caryophyllene in field tests. In our results, the amount of β-caryophyllene was much higher in PAMEX and PAM 3 than in PAM 2, the latter of which was one of the most attractive trees in this experiment.…”
Section: Discussionmentioning
confidence: 95%